Guideline‐compliant prescription of biologicals and possible barriers in dermatological practices in Bavaria. (7th February 2018) - Schielein, M.C.; Tizek, L.; Rotter, M.; Konstantinow, A.; Biedermann, T.; Zink, A.
Abstract: Introduction: Psoriasis and urticaria are chronic inflammatory skin diseases, which account for a substantial socioeconomic burden and severely affect patients' quality of life. According to the respective German guidelines, biologicals can be used for the treatment of severe forms of these diseases. However, only a minority of patients receive this advised treatment. Objective: To analyse the prescription of biologicals according to the German national guidelines for psoriasis and chronic spontaneous urticaria and to assess possible barriers to prescription. Materials and methods: Cross‐sectional, questionnaire‐based study including all Bavarian dermatologists based in private practices. Linear and logistic regression models were used to identify significant influencing factors on the perception of possible barriers. Results: Between January 2017 and February 2017, a total of 137 (of 499) dermatologists participated. Of all patients with moderate to severe psoriasis and chronic spontaneous urticaria, participating dermatologists indicated treating 14.2% and 6.9% with biologicals, respectively. The most prevalent barriers to prescription were the high cost of the therapy, the low reimbursement and the fear of recourse. Analysis showed that age, years spent working in a dermatological hospital and the number of patients treated with moderate to severe psoriasis affect the perception of many barriers. Furthermore, age and barriers related to physician factors and external factors were identified as modifiers to the prescription scheme of dermatologists. Conclusions: The role of clinical education and the importance of external and economic barriers in comparison with medical barriers have to be emphasised. Guideline‐compliant use of biologicals has to be optimised. Further research is needed to ascertain not only a barrier pattern for Bavaria but also for wider settings. Actions based on this for psoriasis are needed to achieve the goal of the WHO Global Psoriasis Report to strengthen the role of patient‐centred care and improve the quality of life of affected patients. Analogue, this applies also for urticaria.